2007
DOI: 10.1186/1477-7525-5-10
|View full text |Cite
|
Sign up to set email alerts
|

Self-report and parent-report of physical and psychosocial well-being in Dutch adolescents with type 1 diabetes in relation to glycemic control

Abstract: Background: To determine physical and psychosocial well-being of adolescents with type 1 diabetes by self-report and parent report and to explore associations with glycemic control and other clinical and socio-demographic characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
46
1
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 35 publications
6
46
1
7
Order By: Relevance
“…The impact of this neurodevelopmental disorder on adolescents' everyday life is also significantly more severe than the impact of a somatic disorder on those with diabetes. These latter subjects display no impairment on their level of quality of life related to their chronic illness, compared to healthy teenagers, findings in agreement with the studies from Laffel et al [21] and de Wit et al [9].…”
Section: Discussionsupporting
confidence: 92%
“…The impact of this neurodevelopmental disorder on adolescents' everyday life is also significantly more severe than the impact of a somatic disorder on those with diabetes. These latter subjects display no impairment on their level of quality of life related to their chronic illness, compared to healthy teenagers, findings in agreement with the studies from Laffel et al [21] and de Wit et al [9].…”
Section: Discussionsupporting
confidence: 92%
“…Others have found that parents might also be better at evaluating primarily observable behavior, while the inner lives of chronically ill children are better evaluated by the children themselves [42]. De Witt et al (2007) [43] did however find parent and child reports on comparable questionnaires measuring psychosocial well-being to be largely concordant, but also found parents to rate their children less favorable with respect to behavioral problems, than children did themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, with respect to diabetes management, adolescents perceive that they are more self-reliant and competent (Mansfield et al, 2004; Ott, Greening, Palardy, Holdreby, & DeBell, 2000) and experience fewer problems with diabetes (de Wit et al, 2007) compared with their parents. Little information is available to indicate whether mothers and fathers would be discrepant in similar ways to their adolescents, as few studies include fathers.…”
Section: Consistency Across Constructs In Parent-adolescent Discrepanmentioning
confidence: 99%